2020
DOI: 10.1177/1948550620969608
|View full text |Cite
|
Sign up to set email alerts
|

Authoritarianism and Social Dominance Predict Annual Increases in Generalized Prejudice

Abstract: Although right-wing authoritarianism (RWA) and social dominance orientation (SDO) are the two most studied individual difference correlates of prejudice, debate remains over their status as enduring constructs that precede generalized prejudice. We contribute to this discussion using 10 annual waves of longitudinal data from a nationwide random sample of adults to investigate the stability and temporal precedence of RWA, SDO, and prejudice among members of an ethnic majority group ( Ns = 23,383–47,217). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 38 publications
1
37
1
4
Order By: Relevance
“…Finally, the sample we use here is not representative of those in the British public who voted in the referendum. Nevertheless, our suggested causal pathway is reasonable given previous research and the relative stability of these orientations (e.g., Osborne et al 2020;Ludeke and Krueger 2013). As this particular event has now passed into history, it will remain for future research to see whether these relationships hold for similar future events.…”
Section: Discussionsupporting
confidence: 54%
“…Finally, the sample we use here is not representative of those in the British public who voted in the referendum. Nevertheless, our suggested causal pathway is reasonable given previous research and the relative stability of these orientations (e.g., Osborne et al 2020;Ludeke and Krueger 2013). As this particular event has now passed into history, it will remain for future research to see whether these relationships hold for similar future events.…”
Section: Discussionsupporting
confidence: 54%
“…Attempts to foster national unity, especially when driven by threat of a pandemic can, however, undermine tolerance and inclusiveness (Foran et al, in press). This is because collective action often relies on amplifying the need for order, compliance, and national unity, and this is often associated with authoritarianism (Osborne, Satherley, Little, & Sibley, 2020). Even in pandemic times, authoritative (or authoritarian) actions by governments can align with preexisting political projects and hierarchical tendencies.…”
Section: National Responses To the Covid-19 Crisis: The Impact Of Politics And Political Leadershipmentioning
confidence: 99%
“…In general, RWA captures preferences for social tradition over progressiveness and SDO captures preferences for intergroup inequality over equality (Duckitt, 2001;Jost et al, 2003). Longitudinal research has shown that RWA and SDO, independently, predict year-to-year increases in prejudice (Osborne et al, 2020).…”
Section: Cyberbullying Cyber-aggression and Cyber-violencementioning
confidence: 99%